Effectiveness of Pandan Wangi (Pandanus amaryllifolius) Leaf Extract on The Quality Of Preserving Salted Duck Eggs: EFEKTIVITAS SARI DAUN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS) TERHADAP KUALITAS PENGAWETAN TELUR ITIK ASIN - Ika Rezvani Aprita; Zulvia Maika Letis; Mulla Kemalawaty; Chairil Anwar; Sukinem; Irmayanti (PT. ROCE WISDOM ACEH, 2024)
Duck eggs are a source of animal protein which generally have lower foam properties and stability compared to purebred chicken eggs, so that the use of duck eggs is still very less compared to purebred chicken eggs in various processed food products. One form of processed food product from duck eggs is salted duck eggs which are obtained by preserving them using salt (salting). In the preservation process, duck eggs are very susceptible to contamination, so alternatives are needed that can inhibit bacterial growth. Fragrant pandan leaves (Pandanus Ammaryllifolius) are believed to be able to suppress the growth of Escherichia Coli and Staphylococcus aureus bacteria, which are 2 types of bacteria that are an indication of food safety. The aim of this research is to determine the effectiveness of adding fragrant pandan leaf extract (Pandanus Amoryllifolius) on the quality of salted duck eggs produced. The method used in this research was a Completely Randomized Design (CRD) model analysis with the concentration factor of adding fragrant pandan leaf extract (Pandanus amaryllifolius). The method used in this research was a Completely Randomized Design (CRD) model analysis with the concentration factor of adding fragrant pandan leaf extract (Pandanus Amaryllifolius) consisting of 5 treatments, namely A = 0%, B = 3% C = 6%, D = 9 %, E = 12%. Each treatment was carried out 4 times to obtain 20 experimental units. Each treatment was carried out 4 times to obtain 20 experimental units. The results of the research showed that the addition of fragrant pandan leaf juice (Pandanus Amoryllifolius) had a significant effect on the organoleptic test of salted eggs, marked by a decrease in weight loss, ranging from 0,14-13,26 with an average value of 3.09. The total microbacterial test ranged between 0.63x10-7 CFU/mL- 16.16 x 10-7 CFU/mL with an average value of 6.15 x 10-7 CFU/mL, and organoleptic test that the panelists still like.